Frequency of stool specimen collection and testing for Clostridioides difficile of hospitalized adults and long-term care facility residents with new-onset diarrhea in Louisville, Kentucky. (July 2022) - Angulo, Frederick J.; Oliva, Senén Peña; Carrico, Ruth; Furmanek, Stephen; Zamparo, Joann; Gonzalez, Elisa; Gray, Sharon; Ford, Kimbal D.; Swerdlow, David; Moïsi, Jennifer C.; Ramirez, Julio
Highlights: New-onset diarrhea was common (1.7/100 inpatient-days, 0.6/100 LTCF-resident-days) Stool specimen collection and Clostridioides difficile testing frequency was low (32%) Low C. difficile testing frequency is indicative of potential C. difficile infection (CDI) underdiagnosis Further studies are needed to confirm the extent of CDI underdiagnosis Abstract: Objectives: This study aimed to determine the stool specimen collection and Clostridioides difficile ( C. difficile ) testing frequency from inpatients and long-term care facility (LTCF) residents with new-onset diarrhea. Methods: A cross-sectional study was conducted in all wards of 9 adult hospitals (3532 beds) and 14 LTCFs (1205 beds) in Louisville, Kentucky to identify new-onset diarrhea (≥3 loose stools in the past 24 h and not present in the preceding 24 h) among Louisville adults via electronic medical record review, nurse interviews, and patient interviews during a 1–2 week observation period in 2018–2019. Results: Among Louisville-resident inpatients, 167 patients with 9731 inpatient-days had new-onset diarrhea (1.7/100 inpatient-days). Stool specimens were collected from 32% (53/167); 12 (23%) specimens were laboratory-confirmed for C. difficile infection (CDI) (12.3 cases/10, 000 inpatient-days). Among LTCF residents, 63 with 10, 402 LTCF resident-days had new-onset diarrhea (0.6/100 LTCF resident-days). Stool specimens were collected from 32% (20/63); 9 (45%) specimens were laboratory-confirmed for CDI (8.6 cases/10, 000 LTCF resident-days). Conclusions: New-onset diarrhea was common among inpatients and LTCF residents. Only one-third of patients with new-onset diarrhea had a stool specimen collected and tested for C. difficile —indicative of a potential CDI underdiagnosis—although, further studies are needed to confirm the extent of CDI underdiagnosis.